Beyond PROX1: transcriptional, epigenetic, and noncoding RNA regulation of lymphatic identity and function - Ducoli, Luca; Detmar, Michael (Developmental cell, 2021)
The lymphatic vascular system acts as the major transportation highway of tissue fluids, and its activation or impairment is associated with a wide range of diseases. There has been increasing interest in understanding the mechanisms that control lymphatic vessel formation (lymphangiogenesis) and function in development and disease. Here, we discuss recent insights into new players whose identification has contributed to deciphering the lymphatic regulatory code. We reveal how lymphatic endothelial cells, the building blocks of lymphatic vessels, utilize their transcriptional, post-transcriptional, and epigenetic portfolio to commit to and maintain their vascular lineage identity and function, with a particular focus on development.